10 Tips for Using Video Analysis More Effectively in Physical Education: Editor: Brian Mosier. Issue 1 (2nd January 2019) - Beseler, Brad; Plumb, Mandy S.
Abstract : In order for video replay to be an effective assessment and teaching tool, a number of steps need to be followed. This article provides some useful tips for physical educators to ensure they are implementing this video technology effectively when teaching the overarm throw.